2008
DOI: 10.5194/hessd-5-219-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation dynamics and soil water balance in a water-limited Mediterranean ecosystem on Sardinia, Italy

Abstract: Mediterranean ecosystems are commonly heterogeneous savanna-like ecosystems, with contrasting plant functional types (PFTs, e.g. grass and woody vegetation) competing for water. Mediterranean ecosystems are also commonly characterized by strong inter-annual rainfall variability , which influences the distributions of PFTs that vary spatially and temporally. An extensive field campaign in a Mediterranean setting was performed with the objective to investigate interactions between vegetation dynamics, soil water… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…It grows commonly in low-calcium soils, whose main constituent is silica [31]. Thus, on the basis of its ecological requirements cork oak may be defined as a thermophilous, hygrophilous, drought-tolerant, heliophilous species [32]. Winter cold is the most limiting factor for its spreading to the more continental interior zones [33].…”
Section: A Brief Description Of the Cork Oak Forest Ecology And Managmentioning
confidence: 99%
“…It grows commonly in low-calcium soils, whose main constituent is silica [31]. Thus, on the basis of its ecological requirements cork oak may be defined as a thermophilous, hygrophilous, drought-tolerant, heliophilous species [32]. Winter cold is the most limiting factor for its spreading to the more continental interior zones [33].…”
Section: A Brief Description Of the Cork Oak Forest Ecology And Managmentioning
confidence: 99%
“…In a study by Ford and Quiring (2013), LAI was used to estimate the effects of dynamic inter-annual vegetation conditions on soil moisture, and they recommended that dynamic, rather than static, LAI parameters should be used to provide better estimates of intensity and duration of drought conditions. Global and regional studies on the causes of variations in vegetation have shown that climatic factors, particularly precipitation and temperature, significantly influence vegetation dynamics (Jiapaer et al, 2015;Liu et al, 2015;Montaldo et al, 2008;20 Tagesson et al, 2015). For instance, Tagesson et al (2015) reported a strong link between inter-annual variation in species composition and rainfall distribution in a semiarid savanna grassland study site in West Africa region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the causes of variations in vegetation have shown that climatic factors, particularly precipitation and temperature, significantly influence vegetation dynamics (Jiapaer et al, 2015;Liu et al, 2015;Montaldo et al, 2008;Tagesson et al, 2015). For instance, Tagesson et al (2015) reported a strong link between inter-annual variation in species composition and 25 rainfall distribution in a semiarid savanna grassland study site in West Africa region.…”
Section: Introductionmentioning
confidence: 99%